Dependence of the elastic modulus of powder coatings on their porosity in electrical contact hardening - Lopata, O.; Smirnov, I.; Zinkovskii, A.; Lopata, L. (Problems of Tribology, 2021)
The relationship between the elastic modulus and the porosity of powder coatings has been investigated for different methods of their deposition. Porosity is the main means of assessing the quality of coatings and depends on the techniques for their production. A decrease in the elastic modulus of coatings after gas flame spraying is due to the presence of porosity to 30%, and after electric arc spraying – to 20%. The electric contact method of forming coatings makes it possible to reduce porosity to 5-6% and so to bring the value of the elastic modulus of coatings closer to that of compact materials.